2020
DOI: 10.21203/rs.3.rs-29119/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual Screening on Indonesian Herbal Compounds as COVID-19 Supportive Therapy: Machine Learning and Pharmacophore Modelling Approaches

Abstract: Background: The latest development of COVID-19 spread in Indonesia has reached 311,176 cases, with 11,374 patients died, updated on October 6, 2020. Unfortunately, these numbers continue to overgrow, and no drug has yet been approved for effective treatment. This study aims to determine the potential candidate compounds in Indonesian herbal medicine as a COVID-19 supportive therapy using a machine learning and pharmacophore modelling approach.Methods: For the machine learning approach, we used three classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Studies in Mexico even orally administered chlorine dioxide (ClO 2 ) in a low dose to prevent/treat COVID-19-related symptoms in relatives living with COVID-19 patients (7,8). iii) Alleviation of symptoms using natural products: This scenario includes a number of natural products such as Indonesian herbal compounds (9), Iran herbal medicine (10), propolis and honey (11), Indian herbs (12), essential oils (13), and traditional Chinese medicine (TCM) (14)(15)(16). Although all of these studies contend that these natural products "are efficacious and safe", these products are not amenable to becoming generally accepted therapeutics worldwide due to regional and cultural characteristics.…”
Section: Editorialmentioning
confidence: 99%
“…Studies in Mexico even orally administered chlorine dioxide (ClO 2 ) in a low dose to prevent/treat COVID-19-related symptoms in relatives living with COVID-19 patients (7,8). iii) Alleviation of symptoms using natural products: This scenario includes a number of natural products such as Indonesian herbal compounds (9), Iran herbal medicine (10), propolis and honey (11), Indian herbs (12), essential oils (13), and traditional Chinese medicine (TCM) (14)(15)(16). Although all of these studies contend that these natural products "are efficacious and safe", these products are not amenable to becoming generally accepted therapeutics worldwide due to regional and cultural characteristics.…”
Section: Editorialmentioning
confidence: 99%
“…We prefer to use the oversampling method over the undersampling method, because in the previous studies with cases of unbalanced data and the same type of data, using oversampling to balance the data is more effective. The result is that the ensemble method model is more robust because oversampling increases the probability of the classes needed to construct the tree during the node splitting process [40]. The oversampling method duplicates the data in the minor class so that the size is the same as the data in the major class.…”
Section: Random Oversamplingmentioning
confidence: 99%
“…(2020), found that Psidium guajava is potential as a candidate of SARS-CoV-2 therapeutic agent. By using combination studies of machine learning, pharmacophore modelling and molecular docking, some of Psidium guajava compounds such as myricetin, quercetin, luteolin, kaempferol, isorhamnetin [6], and Hesperidin [7] shown good activity for 3CL Pro inhibition [8].…”
Section: Introductionmentioning
confidence: 99%
“…8.72 kcal/mol, RMSD value 3.96 Å and inhibition constant value 408.59 nM. The optimum grid center is x= -9.768; y = 11.424; z = 68.935 with 0.375 Å spacing for default setting.…”
mentioning
confidence: 99%